2014
DOI: 10.1007/s12035-014-8947-7
|View full text |Cite
|
Sign up to set email alerts
|

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro

Abstract: In this study, we tried to explore the molecular mechanism that Corilagin protected against herpes simplex virus-1 encephalitis through inhibiting the TLR2 signaling pathways in vivo and in vitro. As a result, Corilagin significantly prevented increase in the levels of TLR2 and its downstream mediators following Malp2 or HSV-1 challenge. On the other hand, in spite of TLR2 knockdown, Corilagin could still significantly suppress the expression of P38 and NEMO, phosphor-P38, and nuclear factor kappa B. The mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…The cells were cultured, passaged, and proliferated in a routine method as in our previous studies. 8,9 Establishment of FXR gene suppression cellular model L02 cells were maintained in medium RPMI-1640 supplemented with 10% FBS for 12 h. Then, in the normal group, the same medium was replaced and the cells continued to be cultured for 48 h. In the model group, the medium was first substituted with 50 μmol/L guggulsterones and 10% FBS modified RPMI-1640 medium for 24 h, and then was replaced with 50 μmol/L guggulsterones and 1% DMSO medium and 10% FBS-modified RPMI-1640 medium for 24 h. In the Emodin group, the medium was first substituted with 50 μmol/L guggulsterones and 10% FBS-modified RPMI-1640 medium for 24 h, and then was replaced with 25 μmol/L Emodin and 10% FBS-modified RPMI-1640 medium for 24 h. Cells were harvested at day 2 after seeding, respectively.…”
Section: Cell Culturementioning
confidence: 99%
“…The cells were cultured, passaged, and proliferated in a routine method as in our previous studies. 8,9 Establishment of FXR gene suppression cellular model L02 cells were maintained in medium RPMI-1640 supplemented with 10% FBS for 12 h. Then, in the normal group, the same medium was replaced and the cells continued to be cultured for 48 h. In the model group, the medium was first substituted with 50 μmol/L guggulsterones and 10% FBS modified RPMI-1640 medium for 24 h, and then was replaced with 50 μmol/L guggulsterones and 1% DMSO medium and 10% FBS-modified RPMI-1640 medium for 24 h. In the Emodin group, the medium was first substituted with 50 μmol/L guggulsterones and 10% FBS-modified RPMI-1640 medium for 24 h, and then was replaced with 25 μmol/L Emodin and 10% FBS-modified RPMI-1640 medium for 24 h. Cells were harvested at day 2 after seeding, respectively.…”
Section: Cell Culturementioning
confidence: 99%
“…It is interesting to note that it was confirmed that Corilagin attenuates lung cell damage induced by cigarette smoke (28). Some of our previous studies on Corilagin have confirmed its effects on ameliorating sepsis (21) as well as its anti-oxidative and anti-inflammatory effects (29) and suppressive effects on HSV-1 encephalitis (30). Moreover, our studies have demonstrated that IL-13 is associated with the multi-target effects of Corilagin on relieving schistosome egg-induced liver fibrosis (12, 32, 33).…”
Section: Introductionmentioning
confidence: 78%
“…GV367-Stat6/NC-EGFP were transfected into the 293T Cell line, and the viral supernatant was harvested after 48 h. RAW264.7 cells were seeded onto 6-well plates and transfected with lentivirus with a multiplicity of infection (MOI) of 80 according to the manufacturer’s instructions. The medium was replaced 6 h later, and then, the cells were grown for up to 72 h. Then, the lentivirus intervened cells were treated with Corilagin, PZQ or LVXF for another 24 h. Overexpression of Stat6 was confirmed by real-time PCR analysis (30).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure abided by our past experiment [22]. Total RNA was isolated from the liver tissues by using RNAiso Plus (Takara, Dalian, China), and reverse transcription was performed following the protocol of kit (TaKaRa Primescript RT Master Mix Perfect Real Time.…”
Section: Methodsmentioning
confidence: 99%